(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Social Media, has different meanings for different people, for some, it’s a buzzword employing no real-world benefits and an impulsive, complex learning curve. Digital communications cope with the key Facebook, YouTube, etc., High-tech evolution is an on-going process growing at a substantial speed with the incessant growth of the Internet, it resulted in intense revolutions of technology which remarkably changed a person’s method of subsistence. Social media marketing is an expression that describes marketing which is executed via social networks, such as online groups, networks, and numerous additional marketing implements to boost responsiveness among their budding consumers. Social Media is a course of action of gaining attention via social media sites.